Atypical Nummular Headache or Circumscribed Migraine: The Utility of Pressure Algometry - Johanna Barón; Cristina Rodríguez; Marina Ruiz; María Isabel Pedraza; Ángel Luis Guerrero; Pascal Madeleine; María Luz Cuadrado; César Fernández-de-las-Peñas (Pain Research and Management)
A peripheral mechanism has been proposed for nummular headache; however, there have been descriptions of atypical features resembling migraine. The authors describe a case in which algometry assessment facilitated the discrimination between atypical nummular headache and circumscribed migraine. A 21-year-old woman presented with a history of focal episodic pain in a circumscribed area on the left frontal region. The algometry study showed a unilateral and diffuse decrease of the pain pressure thresholds with frontal predominance, as has been proposed for migraine patients. This result led the authors to introduce a more specific preventive therapy with topiramate, with significant relief. In conclusion, cartographic investigation of pressure pain sensitivity is a simple tool that can help to differentiate between nummular headache and migraine. Further confirmatory investigations are needed.